A study on trade barrier and export intention of shrimp with special reference to Chennai - KRISHNAMOORTHY, D.; G. DINESH, (The journal of contemporary issues in business and government, 2020)
In a shrimp exporting the SIMP (Seafood import monitoring program), Turtle excluding device, Antidumping, Price fluctuations are the most trade barrier in global market. This paper examines the perspective of trade barriers in exporting shrimp to the other country. This study revealed major trade barrier information on exporting shrimp to US and EU.